PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Jeni; Zulfah; Adityawarman Hidayat; Dwi Viora; Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' understanding of mathematical concepts through the implementation of the Discovery Learning model in fourth-grade students at SD Negeri 002 Langgini. The problem addressed in this research is the low level of students' conceptual understanding in mathematics, as indicated by the number of students who were unable to restate concepts, provide examples, or relate concepts through mathematical representations. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 18 fourth-grade students. Data collection techniques included observation, tests, and documentation. The results showed an increase in students’ understanding of mathematical concepts after implementing the Discovery Learning model. In the pre-cycle, only 33% of students achieved mastery. After the first and second cycles, the percentage of mastery increased significantly. Based on these findings, it can be concluded that the Discovery Learning model is effective in improving students’ understanding of mathematical concepts. This model allows students to learn actively and independently in discovering and understanding mathematical concepts.